The Implementation of Local Wisdom as an Ethnic Conflict Resolution - Hernawan, Wawan; Pienrasmi, Hanindyalaila; Basri, Hasan (Opción, 2019)
Lampung has a plural society from various background of social, politics, educa- tion and culture. This diversity can occur conflict between each other. It is common to happen an ethnic conflict in Lampung. One of the solutions to solve the conflict is mediated by applying local values in their daily life. This local value is known as piil pesenggiri which there are five principles of life in it. Each of these elements of value if it is essentially done well in society will create a peaceful and side-by-side life among ethnic in Lampung. Itcan be seen from the various conflicts that occur and the way they are resolved. One of them is in the district of South Lampung, where there is a conflict between indigenous and immigrant ethnic groups, name- ly between the people of Lampung and Bali. Conflicts that occur due to repeated friction and are not resolved completely. As a result of this, all societies together resolve the conflict by reviving local cultural values as unifying in daily life. This is also strengthened by the provision of a legitimate legal foundation by the local government in supporting the implementation of local cultural wisdom values.